Pengembangan Perangkat Pembelajaran dengan Model Problem Based Learning pada Materi Statistika Kelas VIII SMP - Riska Aprilia; Zetriuslita Zetriuslita; Rezi Ariawan; Lilis Marina Angraini (UIR Press, 2022)
This study aims to produce mathematics learning tools in the form of a syllabus, lesson plans (RPP), and student worksheets (LKPD) with a Problem Based Learning (PBL) model on valid statistical material for class VIII SMP. This development uses a 4-D model consisting of four stages, namely the Define stage, the Design stage, the Develop stage, and the Disermination stage. However, due to the Covid-19 pandemic situation, the 4-D development model was only carried out in three stages, namely: the Define stage (definition), the Design stage (planning), and the Develop stage (development). The data collection instruments used were syllabus, lesson plans, and LKPD validation sheets. The data collection technique used was a non-test technique in the form of a questionnaire validation sheet given to three validators, namely two lecturers of Mathematics Education FKIP UIR and one mathematics teacher at SMP Negeri 1 Singingi. The analysis technique used is descriptive analysis. From the results of the study, the results of the syllabus validation were 88.71% with a very valid category, for RPP of 85.05% very valid category, and for LKPD 86.85% very valid category. Based on this development research, it was obtained that a learning device using the Problem Based Learning model for statistical material for class VIII SMP was tested for validity.